Effectiveness of Zakat Fund Distribution System in Mustahik Education Program (Study Case at the LAZ Yatim Mandiri Center, Surabaya) - Moch Rahmantio Triatmaja (Universitas Darussalam Gontor, 2022)
In Indonesia, the process of improving the quality of education is followed by several inhibiting factors, one of which is the world condition shrouded by the COVID-19 pandemic. This pandemic has an impact on the education sector in Indonesia by increasing the dropout rate. In general, this is rooted in the family's economic crisis during the pandemic. Many parents are unable to pay for education because their income is low and not commensurate with the high cost of education that must be spent. As for the potential of zakat in Indonesia, zakat can be an important instrument capable of being a solution to overcome educational problems if it is interspersed effectively. Therefore, this study intends to explore and attempt to measure the effectiveness of the distribution system of zakat funds on educational programs at one of the National Amil Zakat Institutions, namely LAZ Yatim Mandiri. This study uses a descriptive qualitative method, the techniques used to collect the data are observation, interviews and documentation which were analyzed by triangulation, using data reduction, data presentation, and data conclusions as well as strengthening the analysis with the effectiveness ratio calculation method. The results showed that the distribution system of zakat funds in the education program at LAZ Yatim Mandiri consisted of 6 stages, there are: 1) Determining the mustahik target for the Sa nggar program, 2) Recruiting teachers and determining the location of the sanggar, 3) Program socialization, 4) Recruiting students, 5 ) Acceptance of students, and 6) Monitoring of sanggar students. In addition, this study also shows that the LAZ Yatim Mandiri educational programs, which called the Sanggar Al-Qur'an and the Sanggar Genius, have been effective. This study indirectly shows that the level of effectiveness of the zakat institution program will increase the collection of zakat funds. Furthermore, the benefits of zakat can be felt by many people in need, especially during this pandemic.